Short‐ and long‐term outcomes for single‐port risk‐reducing salpingo‐oophorectomy with and without hysterectomy for women at risk for gynecologic cancer. Issue 2 (February 2021) - Carr, Caitlin E; Chambers, Laura; Jernigan, Amelia Marie; Freeman, Lindsey; Escobar, Pedro F; Michener, Chad M
ABSTRACT : Introduction : Risk‐reducing salpingo‐oophorectomy has been established as one of the most effective strategies in risk reduction for ovarian and breast cancers among women at increased genetic risk. However, there are limited data regarding the single‐port laparoscopic platform in the field of risk‐reducing surgery. Our objective was to describe outcomes after single‐port risk‐reducing salpingo‐oophorectomy with or without hysterectomy for reduction of ovarian, breast, or endometrial cancer risk. Methods : A retrospective, single institution (Canadian Task Force Classification II.2) analysis was performed in women at high genetic or familial risk for ovarian/tubal/primary peritoneal cancer or with personal history of breast cancer who underwent single‐port laparoscopic risk‐reducing salpingo‐oophorectomy with or without hysterectomy between October 2009 and December 2015. Data were collected on patient demographics, surgical procedure and characteristics, intra‐operative findings, and post‐operative outcomes. Results : In total, 187 single‐port laparoscopic surgeries were performed with a median follow‐up of 204 (IQR 25‐749) days. BRCA1/2, Lynch syndrome, or Cowden syndrome was diagnosed in 64.0% of patients. Additionally, 32.1% had a personal history of breast cancer, and 3.2% reported strong family history of ovarian and/or breast cancer. Single‐port risk‐reducing salpingo‐oophorectomy with hysterectomy was performed in 53.5% of patients. The rate of adverse outcomes, including conversion to multiport laparoscopy or laparotomy (1.6%), intra‐operative injury (1.6%), deep vein thrombosis (0.5%), urinary tract infection (2.7%), and/or incisional cellulitis (4.3%) were low. Three patients (1.6%) were diagnosed with malignancy on final pathology. All three patients were BRCA1‐positive and their CA125 values were significantly lower than those without malignancy (p=<0.0001). Conclusions : Single‐port laparoscopy is a safe option for patients undergoing risk‐reducing salpingo‐oophorectomy with or without hysterectomy. Standardized pre‐operative evaluation criteria are needed to determine absolute risk of incidental malignancy, and the risk of identifying a malignancy should be reiterated to patients during pre‐operative counseling.